The Effect of the Think Pair Share Learning Model on Indonesian Language Learning Outcomes in Determining the Main Idea of Paragraphs among Fourth-Grade Students at SDN 040443 Kabanjahe in the 2025/2026 Academic Year - Tania Agatta Br Sembiring; Yunistita Singarimbun; Nurlia Ginting (Asian Journal of Applied Education (AJAE), 2026)
The purpose of this study was to analyze the effect of implementing the Think Pair Share (TPS) learning model on students’ Indonesian language learning outcomes in the topic of determining the main ideas of paragraphs among fourth-grade students at SDN 040443 Kabanjahe. The research was conducted in the 2025/2026 academic year as an effort to improve the effectiveness of the learning process in elementary schools. This study employed a quantitative approach with a Nonequivalent Control Group Design. The research subjects consisted of 50 students, divided into Class IV-A as the experimental group and Class IV-B as the control group. Data were collected using a multiple-choice test instrument that had been tested for validity and reliability. The data were analyzed through prerequisite tests, including normality and homogeneity tests, followed by hypothesis testing. The results showed that the average learning outcomes of students in the experimental class increased from 64.80 to 88.80, while the control class obtained an average score of 68.00. These findings indicate that the Think Pair Share (TPS) learning model has a significant effect on improving students’ learning outcomes and can be used as an alternative learning strategy for Indonesian language instruction in elementary schools.